Skills Development and Graduate Employability in the Tourism and Hospitality Sector of Southwestern Uganda: A Case of Kabale District - Tushabe, Sylivia Byarugaba (Kabale University, 2025)
Despite the expanding demand for skilled professionals in the tourism and hospitality sector, employers consistently express dissatisfaction with the competencies of recent graduates. This skills–employability gap undermines graduates’ capacity to secure gainful employment and limits the sector’s potential for growth. While previous studies have addressed employability in broader contexts, there is a paucity of empirical evidence specific to rural districts in sub-Saharan Africa, where tourism represents a strategic economic pillar. This study investigated the relationship between skills development and graduate employability, with a focus on alumni from higher education institutions (HEIs) in Kabale District, southwestern Uganda. A mixed-methods approach, integrating correlational and case study designs, was employed to capture both statistical relationships and contextual insights. Quantitative data were collected from 400 graduates of three purposively selected HEIs using stratified random sampling (response rate: 89.5%). Qualitative data were obtained through semi-structured interviews with 30 stakeholders, including employers, institutional leaders, lecturers, and officials from the Ministry of Tourism, Wildlife and Antiquities, and the Ministry of Education and Sports (response rate: 83.3%). Quantitative data were analysed using SPSS and SmartPLS version 4 to examine predictive relationships between skill domains and employability outcomes. Qualitative data were thematically analysed using NVivo version 10 to capture stakeholder perspectives on graduate preparedness. In terms of results quantitative analysis revealed that socio-emotional skills (β = 0.492, p < 0.05) and cognitive skills (β = 0.325, p < 0.05) were the strongest predictors of graduate employability, while technical skills exhibited a weaker but statistically significant effect (β = 0.149, p < 0.05). Gender (β = 0.014, p = 0.745) and the type of HEI attended (β = 0.032, p = 0.212) were not significant predictors. Qualitative findings corroborated the statistical results, with stakeholders emphasising the tourism industry’s preference for graduates demonstrating strong interpersonal communication, adaptability, and problem-solving abilities over purely technical competencies. The triangulated findings produced three major contributions: (1) empirically confirming socio-emotional skills as the primary determinant of employability in this sector, (2) generating novel district-specific evidence for policy and practice in southwestern Uganda, and (3) developing conceptual and structural equation models that elucidate the pathways linking skills acquisition to employability outcomes. The study concludes that bridging the tourism and hospitality employability gap requires a comprehensive, sustained approach to skills development, with a stronger emphasis on socio-emotional and cognitive competencies alongside technical expertise. Recommendations include institutionalising lifelong learning and continuous professional development frameworks; introducing structured mentorship schemes and soft skills training into HEI curricula; upgrading training facilities with industry-standard equipment; and adopting graduate certification systems to enhance labour market credibility. Furthermore, reinforcing partnerships between HEIs and industry stakeholders is critical for aligning educational outputs with evolving market demands. Policymakers should embed skill enhancement initiatives into national education and tourism strategies to improve graduate readiness for a dynamic and competitive labour environment